The Intersection of Two Exegetical Types of The Quran - Miftah Khilmi Hidayatulloh; Muhammad Hasnan Nahar (IJISH (International Journal of Islamic Studies and Humanities), 2020)
The research affirmed the intersection of two exegetical types of The Quran. This study also confirmed the existence of the pure Al-tafsīr bi al-ma’thūr and the pure Al-tafsīr bi al-ra’yi. The researchers also presented the character of each type to clarify the difference between these exegetical types. The subject of this research was the exegesis, while the object of research is Al-tafsīr bi al-ma’thūr (tradition-based exegesis), Al-tafsīr bi al-ra’yi (reason-based exegesis) and the intersection between the two exegetical types. In the first step, the researchers explained Al-tafsīr bi al-ma’thūr and Al-tafsīr bi al-ra’yi, then analyzed the scope critically. The researchers compared two exegetical types of the Quran to find the differences and the intersections. The researchers also presented examples of each type of exegesis to sharpen the analysis.